Harnessing Artificial Intelligence to Strengthen Intrusion Detection in Modern Network System (International Journal of Scientific Research and Management (IJSRM), 2025)
The rapid expansion of digital infrastructure, cloud computing, Internet of Things (IoT), and remote work environments has led to a dramatic increase in both the complexity and volume of cyber threats targeting network systems. Traditional Intrusion Detection Systems (IDS), which primarily rely on rule-based or signature-based techniques, have proven to be insufficient in coping with the evolving nature of cyber attacks such as zero-day exploits, polymorphic malware, and advanced persistent threats (APT). These conventional systems suffer from limitations including high false positive rates, delayed response times, and an inability to detect previously unseen or obfuscated attacks. Consequently, there is a critical need for intelligent, adaptive, and proactive solutions that can enhance the capabilities of IDS and strengthen network defense mechanisms. Artificial Intelligence (AI), particularly through its subdomains of Machine Learning (ML) and Deep Learning (DL), offers a promising paradigm shift in how network intrusions are detected and mitigated. By learning from large volumes of network traffic data and continuously adapting to emerging patterns, AI-enhanced IDS can outperform traditional systems in detecting both known and unknown threats. This paper investigates the integration of AI algorithms with IDS, evaluates various AI models on benchmark intrusion detection datasets, and discusses the effectiveness, scalability, and adaptability of these models in real-world network environments. To validate the effectiveness of AI-powered IDS, this study employs two standard datasets—NSL-KDD and CIC-IDS2017—representing diverse and realistic attack scenarios. A range of AI models are implemented, including Logistic Regression, Random Forest, Support Vector Machines, Artificial Neural Networks, Convolutional Neural Networks, and Recurrent Neural Networks. These models are compared based on key performance indicators such as accuracy, F1 score, precision, recall, and false positive rate. The results indicate that deep learning models, particularly CNN and RNN, exhibit superior performance in detecting complex and multi-stage intrusions with high accuracy and low false alarms. The escalating frequency and complexity of cyber attacks in modern network environments have rendered traditional Intrusion Detection Systems (IDS) increasingly inadequate. As digital infrastructure evolves—driven by cloud computing, Internet of Things (IoT), 5G networks, and remote work environments—so too does the threat landscape, demanding more intelligent and adaptive security mechanisms. Conventional IDS technologies, typically rule-based or signature- based, rely on predefined patterns to identify known threats. While they are effective in detecting previously cataloged attacks, they often struggle to identify novel or zero-day threats, and are notorious for generating a high rate of false positives, which reduces their practical usability in real-world scenarios. In response to these limitations, artificial intelligence (AI) has emerged as a transformative solution in the domain of cyber security, particularly in intrusion detection. AI- powered IDS systems, especially those employing machine learning (ML) and deep learning (DL) algorithms, are capable of learning complex patterns from vast volumes of network traffic data, enabling them to detect anomalies, predict new attack strategies, and autonomously adapt to evolving threat behaviors. Unlike static models, AI-enabled detection systems can analyze both known and unknown attack vectors, often identifying malicious activity before it can inflict serious damage. This research investigates the integration of AI techniques into modern IDS frameworks and evaluates their performance through empirical experimentation using benchmark datasets such as NSL-KDD and CIC-IDS2017. These datasets represent a wide range of real-world attack scenarios, encompassing both standard and sophisticated intrusion types. Multiple AI algorithms were implemented and compared, including classical machine learning classifiers such as Logistic Regression (LR), Support Vector Machines (SVM), and Random Forest (RF), alongside advanced deep learning models like Artificial Neural Networks (ANN), Convolutional Neural Networks (CNN), and Recurrent Neural Networks (RNN). A rigorous experimental process was adopted, including data preprocessing, normalization, feature selection using recursive feature elimination and correlation matrices, and model training using k-fold cross-validation. The evaluation metrics included accuracy, precision, recall, F1- score, and false positive rate (FPR), offering a comprehensive assessment of each model’s effectiveness in intrusion detection. The results demonstrated a clear advantage for deep learning models, particularly CNN and RNN, which consistently outperformed traditional models in detection accuracy, generalization ability, and false alarm reduction. RNN models showed exceptional capability in recognizing sequential dependencies in network traffic, making them particularly effective in detecting multi-stage or stealthy intrusions that span multiple time windows. Additionally, the study highlights key challenges associated with implementing AI in real-world IDS, such as the need for computationally intensive resources, difficulty in interpreting deep learning outputs, and the potential susceptibility of models to adversarial attacks. Despite these obstacles, the benefits offered by AI—such as adaptability, self-learning, and real-time threat detection—make it a vital component of future-proof cyber security systems. Furthermore, AI-based IDS solutions open opportunities for automation in cyber security operations, significantly reducing the workload on human analysts and enabling faster response to emerging threats. Beyond performance evaluation, the study explores critical challenges in deploying AI-based IDS in operational networks. These include computational overhead, model interpretability, data labeling constraints, and the risk of adversarial attacks on AI systems. While deep learning models offer high detection capability, their "black-box" nature and resource-intensive training requirements pose barriers to real-time implementation, especially in constrained environments such as edge computing and IoT networks. The paper also outlines future research directions, including the development of lightweight AI models, the use of federated learning for privacy-preserving intrusion detection, and the integration of hybrid systems that combine AI with conventional detection mechanisms. Furthermore, the importance of continual learning and updating of AI models to reflect emerging threats is emphasized. In conclusion, this research highlights the transformative role of AI in modern cyber security frameworks. By enabling intelligent, scalable, and adaptive detection mechanisms, AI has the potential to significantly enhance the resilience of network systems against cyber threats. The findings suggest that AI-powered IDS is not only feasible but necessary to ensure robust protection in today’s dynamic threat landscape. However, successful implementation will depend on overcoming existing challenges and aligning AI development with practical, ethical, and infrastructural considerations in cyber security.